The Consequences of Multiple Simultaneous C-Type Lectin–Ligand Interactions: DCIR Alters the Endo-Lysosomal Routing of DC-SIGN - García-Vallejo, Juan J.; Bloem, Karien; Knippels, Léon M. J.; Garssen, Johan; van Vliet, Sandra J.; van Kooyk, Yvette (Frontiers in Immunology, 2015)
Antigen-presenting cells are equipped with multiple receptors to allow proper pathogen recognition and capture. C-type lectin receptors (CLRs) recognize glycan structures on pathogens and endogenous glycoproteins for internalization and antigen processing and presentation. Often, the glycan specificity of these receptors is overlapping and/or pathogens are decorated with ligands for multiple CLRs, posing the question whether interference or cooperativity within the CLR family exists. Here, we used imaging flow cytometry to investigate the internalization properties of four different CLRs (MR, DC-SIGN, MGL and DCIR) on different APCs, as well as their intracellular routing. Although the internalization score of the investigated CLRs was similar on monocytes, macrophages and dendritic cells (DCs), DCIR internalization rates were lower compared to the other CLRs. Upon triggering, DCIR routed to intracellular compartments outside of the classical endo-lysosomal pathway, resulting in poor CD4+ T cell stimulation. Although DC maturation reduced CLR expression levels, it did not affect their internalization rates. Although CLR internalization appeared to be independently regulated, DC-SIGN routing was affected when DCIR was triggered simultaneously. In conclusion, our results provide new insights for the design of DC-based immunotherapeutic strategies and suggest that DCIR is an inferior target in this respect.